2016
DOI: 10.1111/nph.13883
|View full text |Cite
|
Sign up to set email alerts
|

Cool night‐time temperatures induce the expression ofCONSTANSandFLOWERING LOCUS Tto regulate flowering in Arabidopsis

Abstract: Summary Day length and ambient temperature are major stimuli controlling flowering time. To understand flowering mechanisms in more natural conditions, we explored the effect of daily light and temperature changes on Arabidopsis thaliana.Seedlings were exposed to different day/night temperature and day-length treatments to assess expression changes in flowering genes.Cooler temperature treatments increased CONSTANS (CO) transcript levels at night. Nighttime CO induction was diminished in flowering bhlh (fbh)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 60 publications
2
51
1
Order By: Relevance
“…Although night temperature can affect plant growth and metabolism, influencing phenotypes such as flowering and fruit development3435, adaptive responses to day temperature could be important for survival of heat stress, as the hottest temperature usually occurs around noon to early afternoon and heat is more detrimental to plants under light than in the dark due to photo-oxidative damage36. Thus, the TOC1-mediated timing of PIF4 activation by daytime warm temperature could potentially be important for thermo-adaptation and survival of heat stresses in nature.…”
Section: Discussionmentioning
confidence: 99%
“…Although night temperature can affect plant growth and metabolism, influencing phenotypes such as flowering and fruit development3435, adaptive responses to day temperature could be important for survival of heat stress, as the hottest temperature usually occurs around noon to early afternoon and heat is more detrimental to plants under light than in the dark due to photo-oxidative damage36. Thus, the TOC1-mediated timing of PIF4 activation by daytime warm temperature could potentially be important for thermo-adaptation and survival of heat stresses in nature.…”
Section: Discussionmentioning
confidence: 99%
“…This alteration is closely correlated with the robust enhancement of CO transcription by FBH proteins and a subsequent increase in CO protein abundance during the cooler night. Moreover, the SVP protein functions to repress FT expression at dusk under these conditions, without changing the protein amount (Kinmonth-Schultz et al, 2016) (Fig. 2).…”
Section: The Effect Of Temperature Fluctuations On Ft Inductionmentioning
confidence: 99%
“…Thus, importantly, the effect of temperature fluctuations on flowering appears to be substantially photoperiod-dependent (Fig. 2) (Burghardt et al, 2016; Kinmonth-Schultz et al, 2016). The gene expression profile of FT is markedly influenced by warmer day/cooler night cycles in long days but not in short days (Kinmonth-Schultz et al, 2016).…”
Section: The Effect Of Temperature Fluctuations On Ft Inductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in nature, plants are exposed to considerable temperature fluctuations and temperature differences between days and nights. The importance of taking these temperature oscillations into account is illustrated by a recent study that shows that cool night-time temperatures induces FT expression, likely through SVP and FLMδ (Kinmonth-Schultz et al, 2016). The authors demonstrated that under a temperature regime of 22°/12° C (day/night, long day light conditions), SVP levels remained higher after dusk and into the night.…”
Section: Thermosensitive Floral Timing Under Natural Conditionsmentioning
confidence: 99%